Analisis Kebijakan Kiai dalam Penanaman Nilai-Nilai Trilogi Santri dan Panca Kesadaran Santri di Pondok Pesantren - Khoiriyah, Rizka; Masruroh, Dzurrotul; Jazilurrahman, Jazilurrahman; Aisyah, Nur (Universitas Nurul Jadid, 2022)
Leadership or leadership has been the study of experts and practitioners from time to time and has always been something interesting to study because the theories and approaches continue to develop and evolve. Trilogy of Santri and Awareness of Santri at Pondok Pesantren Nurul Jadid. researchers used qualitative research. That is a study in which data presentation is in the form of words or sentences. This qualitative approach aims to understand the phenomena that occur through a holistic picture and broaden an in-depth understanding of the formation of inculcation of character values. The results of this study are the founder's background in applying the five awareness of the santri, Religious Awareness For Nurul Jadid's students, religious awareness is a starting point that must be instilled in him; Knowledgeable Awareness, Knowledge definitively means knowing the unknown (idrakul majhul),; National and State Awareness The philosophical foundation that underlies KH. Zaini Mun'im; organizational awareness, kiai policy in instilling the values of the trilogy of santri.the cleric's policies in instilling the values of the santri trilogy.